Emotional Regulation Scale for Educational Psychologists (EMOREC) - Guzmán-Torres, Cristian; Aguirre C., Paola; Cuascota, Gabriela; Guamán, Carlos; Jaramillo, Lizeth (Revista Ecos de la Academia, 2025)
Emotional regulation is essential for educational psychologists in their professional practice. It enables them to manage stress, facilitate learning, and promote a positive environment. Additionally, it enhances their ability to respond to students’ needs, foster constructive relationships and promote their own well-being. This article aims to detail the design and validation of the Emotional Regulation Test (EMOREC), which consists of 28 items measuring four dimensions: attention, situation, interpretation, and response. The test was validated by two experts in the field, and its exploratory factor analysis was conducted using data from 86 educational psychology professionals in Ecuador. Statistical analysis using Cronbach’s Alpha demonstrated adequate internal consistency (.921). Two separate norms were constructed (Male/Female) as null hypotheses were rejected for each factor. These norms explained the level of emotional regulation (low, medium, high). Given the limited number of practicing educational psychologists in Ecuador, a larger sample size is recommended for future applications of the EMOREC. This will yield more representative results and enhance its validity across diverse educational and professional contexts.